Go Play Outside! : Tips, Tricks, and Tales from the Trails - Fresco, Nancy; Cable, Molly; Cable, Elizabeth; Cable, Jay (Book collections on Project MUSE., 2021)
"During my thirteen years of Official Parent Experience, I've been asked some variant of this question a surprising number of times -- by new parents, soon-to-be-parents, and not-sure-if-we-want-to-be-parents. Free-spirited young adults seem genuinely worried that if they take on the role of "mom" or "dad" they will be locked forever in a minivan with dark-tinted windows. "Will we still be able to enjoy the great outdoors? The wild places? The adventures?" I can't claim to know everyone's answer, but I do know my own. It's long and complicated, and is covered in myriad ways in this book. It is also short: yes"--